Nilai-Nilai Prinsip Perang dan Perlindungan dalam Perang - Mohd Yusuf DM; Johannes Pangihutan Sipayung; Rubenjos Soros Sipayung; Asmen Ridhol (Dinasti Review Publisher, 2024)
The impact of international armed conflicts on civilians can result in numerous casualties and property damage, as well as the destruction of infrastructure and facilities. This includes the wide geographic scope of international armed conflicts and the socioeconomic impacts on civilians. Therefore, legal protection efforts for civilians in international armed conflicts are crucial, as outlined in the Geneva Conventions of 1949, specifically the Fourth Convention: The Geneva Convention relative to the Protection of Civilian Persons in Time of War. The method used in this study is normative legal research. Based on the research findings, it is evident that war, as one of the most destructive social phenomena, necessitates principles governing conduct during conflicts to minimize human suffering. These principles aim to protect those not directly involved in hostilities and to limit the means and methods of warfare used by conflicting parties. Key principles underpinning international humanitarian law include the Principle of Distinction, the Principle of Proportionality, the Principle of Humanity, and the Principle of Military Necessity. In the context of protection in war, legal instruments such as the Geneva Conventions and Additional Protocols provide a framework for safeguarding those who are not or are no longer participating in hostilities, including prisoners of war, civilians, and medical personnel.